PRODUCTIVE WAQF AS A SUSTAINABLE DEVELOPMENT FINANCING INSTRUMENT - Ainun Barakah (Universitas Nurul Jadid, 2025)
Productive waqf has gained increasing scholarly attention as an Islamic philanthropic instrument capable of addressing sustainable development financing gaps. Despite its growing prominence, the literature remains fragmented across disciplines, geographies, and methodological approaches. This study employs a Systematic Literature Review (SLR) methodology, following PRISMA 2020 guidelines, to synthesize and critically analyze 96 peer-reviewed articles published between 2010 and 2024 retrieved from Scopus, Web of Science, and DOAJ. The review identifies six dominant research themes: (1) governance and institutional management, (2) waqf-based microfinance and poverty alleviation, (3) alignment with the United Nations Sustainable Development Goals (SDGs), (4) sukuk waqf and innovative financing structures, (5) waqf applications in education and healthcare, and (6) digitalization and financial technology integration. Findings reveal critical research gaps, including insufficient empirical evidence on return on investment of waqf assets, lack of cross-country comparative governance analyses, inadequate SDG-aligned metrics, and limited exploration of blockchain-enabled waqf tokenization. Based on these findings, the study proposes a comprehensive future research agenda with specific methodological directions to guide scholars, practitioners, and policymakers in advancing the productive waqf ecosystem. This study contributes to the Islamic economics literature by offering the most updated and methodologically rigorous SLR on productive waqf to date.